Metastasis of colon adenocarcinoma to the mandible: A case report. Issue 1 (26th November 2016) - Kameta, Ayako; Oda, Takaaki; Ogura, Ichiro; Ono, Junya; Kanri, Yoriaki; Okada, Yasuo; Tsuchimochi, Makoto
Abstract: Metastatic tumors to the oral cavity are uncommon. In this article, we report a case of metastatic adenocarcinoma of the colon to the mandible with imaging features. A 73‐year‐old man with a history of colon cancer and liver metastasis was referred to our hospital with a chief complaint of swelling and pain in the right mandible. Panoramic radiograph revealed a radiolucency with ill‐defined margin. Computed tomography showed an osteolytic lesion with cortical bone destruction. Magnetic resonance imaging showed a round‐shaped homogeneous intensity mass expanding from the mandible. Histopathological diagnosis revealed metastatic adenocarcinoma of the colon.